Perceptions of caregivers on the influence of child support grant on children's well-being: a case study of Mpophomeni area in Umgungundlovu, (Peitermaritzburg), KwaZulu Natal - Mazeza, Kudakwashe (My University, 2018)
There have been vast studies on child poverty in South Africa as a result of the numerous programmes that aim to help families maintain the well-being of children. Amongst these programmes is the child support grant (CSG) which was implemented since 1998. The CSG grant is being given to vulnerable (primary) caregivers for the provision of the child’s basic needs. In some families, CSG happens to be their sole income and this constitutes the dark spot this study intends to explore. Hence, I employed qualitative methodology and through explorative research design to investigate the actual influence of the CSG on the recipients’ children. Purposive sampling and snowball sampling were applied to select a sample of 20 caregivers benefiting from CSG, between the age of 21 and 60. In South Africa, KwaZulu-Natal province has been known with high prevalence of HIV and AIDs, as well as poverty amongst blacks, so I chose Mpophomeni in UMgungundlovu district with respect to accessibility and it is a black community. Semi-structured interviews were used to collect data whilst thematic analysis was applied for data analysis. This study reveals that CSG truly constitutes the only source of income for so many families who benefit or are the recipients of the grant. Most caregivers interviewed accepted that they actually invest on CSG as a last resort. As such CSG is used by most caregivers to cover their own needs as they easily get away with it. Also, CSG is used for many other primary caregivers as self-development fund which often are spent on adult education. This study reveals that many caregivers use CSG on expensive hairdressing and alcohol consumption. Participants were asked to comment on this wayward since the government seemed to remain tacit about the worrying situation. It appears as if the government has run out of options or would not want to act. The recipients suggested adoption of vouchers instead of cash which can only be used in certain set of shops. But would this solve the problem where the children beneficiaries are neglected by their caregivers? What other possible options would the government adopt to ensure that the money is spent accordingly? This study is more of thought-provoking, as it opens up a dialogue, as well as calling subsequent researchers to engage this topic further for clearer policy insights. However, this study concluded that CSG though contributes to the wellbeing of the recipient children and provides income to access their basic needs, yet a lot of violation happens without check. The study recommends that the Department of Social Development and local governments may partner to engage further in monitoring and evaluating with an aim to eradicate poverty. The social workers and SASSA officials need to work together in monitoring and reviewing CSG utilisation. Hence, the findings of this study contribute to the intervention measures leading to the use of CSG to maintain the child’s well-being in South Africa.
A Research Report Presented to Department of Social Work, School of Human and Community Development, Faculty of Humanities, The University of the Witwatersrand In partial fulfilment of the requirements for the degree of Master of Arts in the field of Social Development, September 2018
Keywords: Child support--Government policy--South Africa; Caregivers--South Africa; Child welfare--South Africa; South Africa--Social policy